Analysis of the final fights of the judo tournament at Rio 2016 Olympic Games - Boguszewski, D. (Journal of Combat Sports and Martial Arts, 2016)
Introduction Analyses of the actions taken at start by the contestants of martial sports can deliver a considerable amount of valuable information for the coaching staff. The aim of this study was to establish the combat dynamics and to characterise the most frequent offensive and defensive actions taken by the finalists of the judo tournament at Rio de Janeiro Olympics. Materials and Methods The research has been executed on the basis of the recordings of 14 final combats at 2016 Olympic Games. 28 contestants, representing 17 countries, took part in the tournament. The analysis was performed on the basis of the Kalina`s method of combat dynamics measurement, with an author`s modification. The offensive actions were classified according to Kodokan Judo classification (throws: hand throws, hip throws, leg throws, and grapples: holds, chokes, levers). The conventional division on 12 defensive techniques was adopted for the purpose of their analysis and presentation. Results The activeness of the contestants amounted, on average, to 0.33, which means that for 2/3 of their combats, judokas did not take any offensive or defensive actions. No statistically significant differences in any element of combat dynamics were observed between men and women. By comparing gold and silver medal winners, it was determined that the final combats winners showed significantly higher effectiveness of attack and defensive actions as well as general combat dynamics. Leg and hand throws were the most frequent offensive actions. However, holds were the most effective actions (50%). Hand block was the most frequently used defensive technique. Conclusions (1) The low level of activeness and offensive activeness demonstrated by the judokas (including gold medal winners) indicates that the contestants made fewer attempts to gain advantage through their technical actions. (2) The final combat winners executed leg throws nearly four times more often. The effectiveness of these actions was very high (30%). Whereas, the silver medal winners much more often made attempts of hand and hip throws, which were ineffective.